Heterodimerization of TFAP2 pioneer factors drives epigenomic remodeling during neural crest specification - Rothstein, Megan; Simoes-Costa, Marcos

(untitled) (Genome Research, 2020)
Cell fate commitment involves the progressive restriction of developmental potential. Recent studies have shown that this process requires not only shifts in gene expression but also an extensive remodeling of the epigenomic landscape. To examine how chromatin states are reorganized during cellular specification in an in vivo system, we examined the function of pioneer factor TFAP2A at discrete stages of neural crest development. Our results show that TFAP2A activates distinct sets of genomic regions during induction of the neural plate border and specification of neural crest cells. Genomic occupancy analysis revealed that the repertoire of TFAP2A targets depends upon its dimerization with paralogous proteins TFAP2C and TFAP2B. During gastrula stages, TFAP2A/C heterodimers activate components of the neural plate border induction program. As neurulation begins, TFAP2A trades partners, and TFAP2A/B heterodimers reorganize the epigenomic landscape of progenitor cells to promote neural crest specification. We propose that this molecular switch acts to drive progressive cell commitment, remodeling the epigenomic landscape to define the presumptive neural crest. Our findings show how pioneer factors regulate distinct genomic targets in a stage-specific manner and highlight how paralogy can serve as an evolutionary strategy to diversify the function of the regulators that control embryonic development.